PENGARUH UMUR MASAK POLONG TERHADAP VIABILITAS DAN VIGOR BENIH BEBERAPA AKSESI BENGKUANG (Pachyrhizus erosus) - Krisnawati, Ayda; Adie, M Muchlish (BERITA BIOLOGI, 2018)
Seed germination uniformity and simultaneity of yam bean was related to pod maturity. A total of ten accessions of yam bean was planted at Kendalpayak Research Station, Malang (Indonesia) from May to October 2016. Yam bean pods of each accession were harvested at three developmental stages, i.e. full-size green pods, yellow pods, and brown/black pods. The experiment was conducted using a completely randomized factorial design with three replications. The first factor was pod maturity and the second factor was yam bean accessions. Significant interactions between pod maturities with accessions were found on characters of epicotyl length, leaf length, leaf width, root dry weight, maximum growth potential, and germination rate at the 10th days of observation. The pod maturity at yellow stage gave the highest maximum growth potential and germination rate. The average germination rate of yellow pods was 8.15% per day which was, higher than those of green pods (3.83% per day) as well as black pods (3.73% per day). These yellow pods have optimal germination growth of compared to those of green as well as black pods. The practical implication of this research is the use of yellow pods as recommended seed source for yam bean cultivation.Â